Variability of retinopathy consequent upon novel mutations in LAMA1. (3rd September 2022) - Schiff, Elena R.; Aychoua, Nancy; Nutan, Savita; Davagnanam, Indran; Moore, Anthony T.; Robson, A. G.; Patel, C. K.; Webster, Andrew R.; Arno, Gavin
ABSTRACT: Purpose: Bi-allelic mutations in LAMA1 (laminin 1) (OMIM # 150320) cause Poretti-Boltshauser Syndrome (PTBHS), a rare non-progressive cerebellar dysplasia disorder with ophthalmic manifestations including oculomotor apraxia, high myopia, and retinal dystrophy. Only 38 variants, nearly all loss of function have been reported. Here, we describe novel LAMA1 variants and detailed retinal manifestations in two unrelated families. Methods: Whole-genome sequencing was conducted on three siblings of a consanguineous family with myopia and retinal dystrophy and on a child from an unrelated non-consanguineous couple. Clinical evaluation included full ophthalmic examination, detailed colour, autofluorescence retinal imaging, retinal optical coherence tomography (OCT), fluorescein angiography under anesthesia, and pattern and full-field electroretinography. Results: Genetic analysis revealed a novel homozygous LAMA1 frameshift variant, c.1492del p.(Arg498Glyfs *25), in the affected siblings in family 1 and a novel frameshift c.3065del p.(Gly1022Valfs *2) and a deletion spanning exons 17–23 in an unrelated individual in family 2. Two of the three siblings and the unrelated child had oculomotor apraxia in childhood; none of the siblings had symptoms of other neurological dysfunction as adults. All four had myopia. The affected siblings had a qualitatively similar retinopathy of wide-ranging severity. The unrelated patient had a severe abnormality of retinal vascular development, which resulted in vitreous haemorrhage and neovascular glaucoma in the left eye and a rhegmatogenous retinal detachment in the right eye. Conclusions: This report describes the detailed retinal structural and functional consequences of LAMA1 deficiency in four patients from two families, and these exhibit significant variability with evidence of both retinal dystrophy and abnormal and incomplete retinal vascularisation.